A Patient Informed Qualitative Program Evaluation of an Internet-Based Chronic Pain Treatment - Pamela L. Holens; Adair Libbrecht; Michelle Paluszek; Alyssa Romaniuk; Brent Joyal; Jeremiah Buhler; Luigi Imbrogno (Taylor & Francis Group, 2019)
An innovative, Internet-based chronic pain treatment tailored to a military and police population was developed using Acceptance and Commitment Therapy (ACT) as a model. The treatment was recently evaluated in randomized controlled trial and found to be superior to treatment as usual in terms of increasing patients' levels of pain acceptance, decreasing their pain-related catastrophizing, and decreasing their levels of kinesiophobia. In an effort to further increase the efficacy of the treatment, we enlisted patient feedback about the program through a series of focus groups. Participants who had previously completed the online treatment were recruited to participate in a series of focus groups designed to qualitatively evaluate the treatment and offer suggestions for improvements for future versions of the program. Participatory Action Research methodology was used to conduct this study and data were examined using interpretive thematic analysis. Three main themes arose: suggestions for improving the technological "friendliness" of the online program, suggestions for improving the sequencing of content, and suggestions for greater tailoring of the content to the sensitivities of the target population. As an example of the latter, participants suggested removal of the "attending your own funeral" exercise from the values module due to sensitivities around death and dying. Future directions, based on patient feedback, are outlined.